Critique and Analysis of the Book “Language, Context and Text: Aspects of Language in a Social-Semiotic Perspective” - Sepideh Abdolkarimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present article is the result of a critical look at the book “Language, Context and Text: Aspects of Language in a Social-Semiotic Perspective” which is translated to Persian by Dr. Mojtaba Monshizadeh and Dr. Tahereh Ishani. Due to the fact that functional approach to linguistic studies in Iran has gained less attention than generative and cognitive approaches, lack of the presence of such a book in Persian, introducing functional approach to language researchers interested in this approach, was strongly felt. For this reason, translators’ attempt is admirable. One of the challenges translators has faced, has been equivalent choices for technical terms in the named approach and the absence of books in this field in Persian has resulted in the present situation which shows lack of Persian sources in functional linguistics. Other difficulties the translators faced have resulted in the emergence of cases which in their own turn require the revision of the book. Therefore, this article is the introduction of the book, its sections and chapters, as well as its strong and weak points.